Study On The Implementation of Drainage System at Universiti Tun Hussein Onn Malaysia (UTHM): Kajian Perlaksanaan Sistem Saliran di Universiti Tun Hussein Onn Malaysia (UTHM) - Ismail, Mohd Luqman; Shareh Musa, Sharifah Meryam (Journal of Techno-Social, 2021)
Abstract: Drainage systems play an important role in the development of managing surface runoff water. This is because without proper management of the drainage system, it can cause flooding in the area. Universiti Tun Hussein Onn Malaysia (UTHM) has suffered floods and caused significant losses. Therefore, the purpose of this article is to study the types of drainage systems available around the UTHM area. In this regard, semi-structured interviews were conducted with a number of respondents from the Development and Maintenance Office UTHM to study the problems of each existing drainage system around the area and to look at ways of improving the existing drainage system. The types of drainage systems available at UTHM have been identified as conventional drainage systems, Urban Stormwater Management Manual (MSMA), monsoon drainage, main drainage and land drainage. Problems such as drainage system, waste and clogged drainage also being identified. Among the improvements identified are replacing MSMA with open drainage. In conclusion, the study of drainage system implementation at UTHM can provide a clearer picture of the drainage system used around the study area.